Accumulation and temporal changes of PCDD/Fs and dioxin-like PCBs in finless porpoises (Neophocaena asiaeorientalis) from Korean coastal waters: Tracking the effectiveness of regulation. Issue 1 (15th April 2016) - Jeong, Yunsun; Kim, Sang-Jo; Shin, Kyung-Hoon; Hwang, Seung Yong; An, Yong-Rock; Moon, Hyo-Bang
Abstract: Temporal trend studies are useful to evaluate the effectiveness of regulations on local pollutants. The emission of polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) and dioxin-like polychlorinated biphenyls (PCBs) has been regulated by the Korean government in accordance with the Stockholm Convention. The accumulation and temporal trends of PCDD/Fs and dioxin-like PCBs were investigated in finless porpoises ( Neophocaena asiaeorientalis ) collected in Korean waters. Median concentrations of PCDDs, PCDFs, non- ortho PCBs, and mono- ortho PCBs were 1.0, 1.1, 0.1, and 1.8 pg TEQ/g lipid weight, respectively, which were lower than threshold values for marine mammals. Age- and sex-dependent accumulation patterns were found for PCDFs and DL-PCBs. Temporal trends in finless porpoises collected between 2003 and 2010 showed significant reduction rates of 57%, 54%, 69%, and 60% for PCDDs, PCDFs, non- ortho PCBs, and mono- ortho PCBs, respectively. Our results suggest that the regulations on dioxin-like contaminants have been effective for marine mammals in Korea. Graphical abstract: Highlights: TEQ concentrations in finless porpoises were lower than the threshold values for marine mammals. Age and sex-dependent accumulation pattern were found for dioxin-like contaminants. Greater than 50% reduction rates were observed for PCDD/Fs and dioxin-like PCBs in time-gap porpoise samples. Regulation on PCDD/Fs has been effective for marine mammals in Korea.